Theoretical model that explain the knowledge ofthe CSE Program in Special Education Teachers: A bayesian approach - Solórzano Salas, María Julieta (2024)
This study introduces new evidence of the theoretical model that connects21 theoretical hypotheses of personal experience with sexual educationknowledge. Participants were 82 Special Education students with acomparison group of 55 female students from Psychology and NaturalSciences Education studying special education. This correlational andexploratory study proposes an analysis path analyzed with a frequentistapproach. It presents new empirical evidence from a Bayesian approach’stheoretical and methodological assumptions that offer estimates similarto the real values. The information in the model can be used to guide theeducation of Latinas who are Special Education teachers to identify otheraspects that condition their teaching.